Health impact assessment for promoting sustainable development: the HIA4SD project. Issue 3 (3rd May 2020) - Winkler, Mirko S.; Adongo, Philip B.; Binka, Fred; Brugger, Fritz; Diagbouga, Serge; Macete, Eusebio; Munguambe, Khátia; Okumu, Fredros
ABSTRACT: Health is central to sustainable development, and thus a cross-cutting issue of the Sustainable Development Goal (SDG) 2030 agenda. Natural resource extraction projects in Africa have considerable potential to impact on health-related targets of the SDGs. This paper introduces the rationale and organization of the HIA4SD Project; a 6-year research for development (r4d) project that aims to inform and facilitate a policy dialogue at the national and international level on whether current regulatory approaches to impact assessment in Africa promote sustainable development, placing emphasis on SDG3 Good Health and Well-being . The HIA4SD Project has a focus on large-scale natural resource extraction projects and is implemented in four African countries, namely Burkina Faso, Ghana, Mozambique and Tanzania.